2003
DOI: 10.2355/isijinternational.43.1100
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Toughening in Ferritic Iron by Solute Copper at Low Temperature

Abstract: The ductile-to-brittle transition (DBT) and plastic deformation behaviors were investigated in Fe-(0ϳ2)mass%Cu alloys to understand the effect of solute Cu on the mechanical properties of ferritic iron. The DBT temperature of ferritic iron in Charpy impact test was lowered by the solute Cu although the hardness at room temperature was increased owing to solid solution hardening. Tensile tests revealed that the yield stress of the Fe-1mass%Cu alloy becomes smaller than that of the Fe-0mass%Cu alloy in the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…However, in the case of the 35 ppm specimen, the sharp transition was not observed, and its absorbed energy gradually decreased from 450 to 400 K. Obviously, the ductile-brittle transition temperature (DBTT) increased with increasing hydrogen concentrations, and the fracture mechanisms varied with hydrogen concentration. It is of interest to note that the DBTTs of Mg are higher than those for iron and steel, whose DBTTs are generally lower than 300 K. [20][21][22] The high DBTT of Mg may be closely associated with an activity of non-basal slips, whose critical resolved shear stress (CRSS) significantly decreases with increasing temperature at around 423-523 K.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of the 35 ppm specimen, the sharp transition was not observed, and its absorbed energy gradually decreased from 450 to 400 K. Obviously, the ductile-brittle transition temperature (DBTT) increased with increasing hydrogen concentrations, and the fracture mechanisms varied with hydrogen concentration. It is of interest to note that the DBTTs of Mg are higher than those for iron and steel, whose DBTTs are generally lower than 300 K. [20][21][22] The high DBTT of Mg may be closely associated with an activity of non-basal slips, whose critical resolved shear stress (CRSS) significantly decreases with increasing temperature at around 423-523 K.…”
Section: Resultsmentioning
confidence: 99%
“…2 shows a change in the hardness of the specimen as a function of the aging time. According to (Syarif et al, 2003), the hardening mechanism of the asquenched specimen was attributed to the solid solution hardening of supersaturated Cu atoms within the ferritic matrix, which resulted from the massive austenite-to-ferrite transformation. The hardness of the aged specimens gradually increased from HV 180 to HV 300 at 200 s before they gradually decreased with increased aging time.…”
Section: Methodsmentioning
confidence: 99%
“…Both mechanisms can increase the yield strength of steels, although the former is more effective. Syarif et al (2000;2003) also reported that Cu in solid solution can also decrease the ductile-to-brittle transition temperature of ferritic iron, increase the hardness of iron, and improve the strength of steel without diminishing its toughness.…”
Section: Introductionmentioning
confidence: 99%
“…It is due to the thermally activated process of dislocation glide, overcoming a relatively higher Peierls potential in ferritic steels with bcc structures than that in austenitic steels with fcc structures in which the Peierls potential is inevitably low. The increase in the yield stress with decreasing temperature is suppressed by adding particular solid solution elements such as silicon, 1,2) nickel 2) and copper, 3) and then the yield stress becomes lower than that of pure iron at low temperatures. The effect is known as solid solution softening.…”
Section: Introductionmentioning
confidence: 99%